2000
DOI: 10.1085/jgp.116.3.327
|View full text |Cite|
|
Sign up to set email alerts
|

The Extracellular Linker of Muscle Acetylcholine Receptor Channels Is a Gating Control Element

Abstract: We describe the functional consequences of mutations in the linker between the second and third transmembrane segments (M2–M3L) of muscle acetylcholine receptors at the single-channel level. Hydrophobic mutations (Ile, Cys, and Phe) placed near the middle of the linker of the α subunit (αS269) prolong apparent openings elicited by low concentrations of acetylcholine (ACh), whereas hydrophilic mutations (Asp, Lys, and Gln) are without effect. Because the gating kinetics of the αS269I receptor (a congenital myas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 59 publications
9
127
0
Order By: Relevance
“…To analyze a given channel, discrete Markov models (8)(9)(10)(11)(12)(13)(14)(15)(16)) are fit to patch-clamp recordings of its current. However, it is known that different models can make identical predictions of steady-state gating statistics (17,18), so that attempts to find the best-fitting model can uncover many models that all fit equally well.…”
Section: Using Independent Open-to-closed Transitions To Simplify Aggmentioning
confidence: 99%
“…To analyze a given channel, discrete Markov models (8)(9)(10)(11)(12)(13)(14)(15)(16)) are fit to patch-clamp recordings of its current. However, it is known that different models can make identical predictions of steady-state gating statistics (17,18), so that attempts to find the best-fitting model can uncover many models that all fit equally well.…”
Section: Using Independent Open-to-closed Transitions To Simplify Aggmentioning
confidence: 99%
“…For WT neuromuscular AChRs activated by ACh (␣ Ϸ 1,700 s Ϫ1 and ␤͞k Ϫ2 Ϸ 1), k* (Ϸ850 s Ϫ1 ) is much greater than (Ϸ70 s Ϫ1 ; see below). Thus, at the neuromuscular synapse, bursts terminate mainly by agonist dissociation from A 2 C, and b Ϸ 1͞k* Ϸ 1.2 ms (13,18).…”
Section: Resultsmentioning
confidence: 99%
“…The fast-opening constructs had mutations at position D97 [in loop 5, near the transmitter binding site (12)] in both ␣-subunits. Where noted, a second fast-opening mutation, ␣S269I, in the extracellular linker (13), was also present. The slow-closing constructs had side-chain substitutions at position L265 or S268 in the membrane domain of the ␦-subunit (9).…”
Section: Methodsmentioning
confidence: 93%
“…Our laboratory previously used this approach to demonstrate a glycine-induced increase in the surface exposure of six continuous residues (Arg 271 -Lys 276 ) in the GlyR M2-M3 linker domain (14). These residues lie mid-way between the binding site and the activation gate (7), and it is now well established that they experience a conformational change that is crucial for the activation of GlyRs (14 -18), ␥-aminobutyric acid, type A receptors (19 -24), and nAChRs (7,(25)(26)(27). A structural study of the Torpedo nAChR has shown recently (4) that these residues form an extramembranous extension to the M2 ␣-helix.…”
mentioning
confidence: 99%